Synthesis of some new thiazolo[4,5-b]pyridin-2-ones and research of their anti-inflammatory activity - T. I. Chaban (The State Expert Center of the Ministry of Health of Ukraine, 2019)
In modern theoretical and clinical medicine inflammation problem remains one of the main.Deregulation of inflammatory processes leads to specific pathologies.There is a significant amount of drugs used to treat inflammation. But all of them have varying degrees of ulcerogenic properties. To overcome these limitations search is ongoing throughout the World to find new effective and safe anti-inflammatory agent. Therefore, of course, the synthesis of thiazolidines annelated with the pyridine cycle and the study of their anti-inflammatory properties is an interesting and relevant area. The objective of the present work was to synthesize a series of novel thiazolo[4,5-b]pyridine-2-ones by the structural modification of the (5,7-dimethyl-2-oxo-thiazolo[4,5-b]pyridine-3-yl)-acetic acid hydrazide for further pharmacological screening in vivo as anti-inflammatory activities. The objects of the study were thiazolo[4,5-b]pyridines, obtained by the structural modification of the (5,7-dimethyl-2-oxo-thiazolo[4,5-b]pyridine-3-yl)-acetic acid hydrazide. Anti-inflammatory activity was evaluated using carrageenan induced rat paw edema method in rats In vivo studies were carried out for anti-inflammatory activity employing the carrageenan-induced rat paw edema method. Anti-inflammatory activity was defined by measuring the paw edema volume 4 h after the carrageenan injection.The NSAID drug Ibuprofen in effective therapeutic doses were tested inparallel as an activity references. Inhibition of the inflammatory response was expressed as a percentage of the paw volume reduction. Studies of anti-inflammatory activity showed that the synthesized compounds had pronounced diuretic properties, and some of them according to activity indicators were approaching or exceeding comparative preparations. The results of the anti-inflammatory activity of the synthesized compounds derivatives (5,7-dimethyl-2-oxo-thiazolo[4,5-b]pyridine-3-yl)-acetic acid hydrazide show the potential for the search for anti-inflammatory agents among thiazolo[4,5-b]pyridine-2-ones.